Mobile Commerce Pemasaran Produk Olahan Kelompok Wanita Tani (KWT) Flamboyan Berbasis Android Di Desa Kalirejo - Nungsiyati Nungsiyati; Devi Fitriyana; Muhamad Muslihudin (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2022)
The Women Farmers Group (KWT) is a group of farmers who empower women to build an agricultural group. The activities of the farmer groups are agricultural cultivation and processing of agricultural products which can be useful for increasing farmers' income. However, the current income of farmers is still low due to a lack of media transactions and promotions. One of the ways to increase agricultural output is by utilizing farmer groups. This research was conducted at the Flamboyan Women Farmers Group (KWT), which is a group of women in Kalirejo Village, Kalirejo District, Central Lampung Regency who have agricultural products that are processed into food products. The KWT has only been established for about a year and has ten members. However, KWT Flamboyan has not been able to promote its products widely in other regions. Until now, the promotion has been ineffective because it was done when there was a gathering. Therefore, to help increase sales of processed agricultural products. This study uses Android-based M-commerce as a medium for the transaction, promotion, communication, and information to increase the income of the farmer group. Researchers used a structured prototyping system development method with the interaction and system users and used a fishbone research framework to identify causes and effects in the group. In the discussion, the researcher uses the Context Diagram system design, Data Flow Diagrams (DFD), interface design as an illustration of the information display design between the user and the system, the implementation of the program description of the interface design then the program is made and the analysis of the test results of this system is made to test the pages has been made and then tested whether the system needs to be evaluated or not. The results obtained are in the form of an Android-based M-commerce sales application that can be accessed online which can serve online sales transactions and can reduce expenses.